Telocytes in minor salivary glands of primary Sjögren's syndrome: association with the extent of inflammation and ectopic lymphoid neogenesis - Alunno, Alessia; Ibba‐Manneschi, Lidia; Bistoni, Onelia; Rosa, Irene; Caterbi, Sara; Gerli, Roberto; Manetti, Mirko (Journal of cellular and molecular medicine, 2015)
It has been recently reported that telocytes, a stromal (interstitial) cell subset involved in the control of local tissue homeostasis, are hampered in the target organs of inflammatory/autoimmune disorders. Since no data concerning telocytes in minor salivary glands (MSGs) are currently available, aim of the study was to evaluate telocyte distribution in MSGs with normal architecture, non‐specific chronic sialadenitis (NSCS) and primary Sjögren's syndrome (pSS)‐focal lymphocytic sialadenitis. Twelve patients with pSS and 16 sicca non‐pSS subjects were enrolled in the study. MSGs were evaluated by haematoxylin and eosin staining and immunofluorescence for CD3/CD20 and CD21 to assess focus score, Tarpley biopsy score, T/B cell segregation and germinal center (GC)‐like structures. Telocytes were identified by immunoperoxidase‐based immunohistochemistry for CD34 and CD34/platelet‐derived growth factor receptor α double immunofluorescence. Telocytes were numerous in the stromal compartment of normal MSGs, where their long cytoplasmic processes surrounded vessels and encircled both the excretory ducts and the secretory units. In NSCS, despite the presence of a certain degree of inflammation, telocytes were normally represented. Conversely, telocytes were markedly reduced in MSGs from pSS patients compared to normal and NSCS MSGs. Such a decrease was associated with both worsening of glandular inflammation and progression of ectopic lymphoid neogenesis, periductal telocytes being reduced in the presence of smaller inflammatory foci and completely absent in the presence of GC‐like structures. Our findings suggest that a loss of MSG telocytes might have important pathophysiological implications in pSS. The specific pro‐inflammatory cytokine milieu of pSS MSGs might be one of the causes of telocyte loss.